USING THE STRATEGIC SATELLITE IMAGERY METHODS FOR AGRICULTURAL LAND MONITORING - Hulko, О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
With the development of society and the increasing impact of human activities on the Earth's ecological system, it is necessary to find new methods of managing natural resources while also satisfying human needs. Nowadays, space imagery is the primary method of obtaining information through various carriers, with the support of survey equipment. This data is widely used in cartography to solve problems in all areas of science and technology, as well as to create geographic information systems. Every year, the volume of products related to mapping and geoinformation is expanding, and new areas for using this information are emerging. For several decades, space imagery has been characterized by acquiring aerial data with very high spatial resolution (<1 m), an increase in spectral resolution of imaging systems, and the implementation of spectral imagery. A remote sensing model is a system that receives and converts input signals of the electromagnetic spectrum into output signals that form images or point source data about objects on the ground. In recent decades, remote sensing has been particularly useful for obtaining informative data about the earth's surface. Consequently, remote sensing can provide natural characteristics of soil types, vegetation, and more. The information obtained through aerospace remote sensing is widely used in many countries around the world for finding minerals, assessing the rural potential of regions and countries, analyzing agricultural land, identifying types and species of crops, forecasting yields, and monitoring soils and pastures. The soil science crisis in Ukraine was caused by the administrative-command economy in the past.